PROBLEMS IN TRANSLATION - Olimova Muslima (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article delves into the complexities of translation, highlighting challenges like linguistic differences, cultural nuances, and technical terminology. It offers insights into strategies for addressing these hurdles effectively in the translation process.